Benthic controls of resuspension in UK shelf seas: Implications for resuspension frequency. (1st September 2019) - Thompson, C.E.L.; Williams, M.E.; Amoudry, L.; Hull, T.; Reynolds, S.; Panton, A.; Fones, G.R.
Abstract: In situ measurements and ship-based resuspension experiments using annular flumes are used to determine sediment stability and critical erosion thresholds for four sites with significantly different sediment characteristics, located in the Celtic Sea at water depths of 100 m. Seasonal and spatial variability of sediment characteristics and erodability is examined, and found to be the result of changes in percentage of organic carbon in the surface sediments (R 2 = 0.82) and bulk density (R 2 = 0.73) respectively when individual characteristic bed parameters are considered. Principal component analysis and linear regression analysis are used to determine a predictive model for erosion threshold in the Celtic Sea (R 2 = 0.99), based on grain size, sorting, kurtosis, bulk density, porosity, percentage fines, organic carbon content and chlorophyll a concentration. Physical sediment characteristics were found to be more significant controls of bed stability than biological factors. Local hydrodynamic conditions are used to determine the likelihood and frequency of resuspension given these critical erosion thresholds. Resuspension is driven by tidal currents, and is common year-round, leading to a constant re-working of bed sediments in particular at the muddier sites. This is confirmed by in situ measurements of suspended sediment concentration. Highlights: Bed erodibility in the Celtic Sea a function of organic carbon and bulk density. Predicting erosion threshold requires emphasis on physical sediment characteristics. Bed sediments re-worked year round by tidal resuspension, enhanced by winter waves.